Almost as helpful as good theory: some conceptual possibilities for the online classroom - David , Mike; Denning , Kate (Research in Learning Technology, 1970)
Current interest in the use of Communications and Information Technology (C&IT) in higher education and other settings is at a high level (for example, Framework V: Towards a User-Friendly Information Society; the ESRC Programme PACCIT) and while universities - in response to the Dearing Report - begin to exercise effort in restructuring course delivery methods to take advantage of the technology, there is a danger that the issue of the changes in the social dynamics that are a direct consequence of the transition from actual space to virtual space will be overlooked. Some work has been undertaken in this area (notably Rheingold, 1991; Cook, 1995; McConnell, Hardy and Hodgson, 1996) but there is need for additional research if we are to identify a clearer sense of how effective online learning might manifest itself.DOI:10.1080/0968776010090207